PENGEMBANGAN KURIKULUM PAI BERBASIS PENDIDIKAN MULTIKULTURAL PERSPEKTIF ISLAM - Ahmad Buchori Muslim (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2021)
The condition of education in Indonesia includes inadequate education for people in Indonesia who are more than one and have a cultural diversity. Therefore, it is necessary to transform in educational knowledge in Indonesia. Multicultural education knowledge as a substitute for monocultural educational knowledge. The importance of education in multiculturalism is to some extent and get a positive response from the relevant parties and authorities. This is evidenced by the Law of the Republic of Indonesia No. 20 of 2003 concerning the National Education System which provides human rights values. So these values are used as one of the implementation of National Education, as education is held in a fair nature and does not discriminate by upholding human rights, religious values, cultural values and national diversity. Therefore, the implementation of education requires a curriculum, and multicultural values must be used as a basis for planning, implementing and evaluating the curriculum to an educational institution either in the form of schools, madrassas, and pesantren. Islamic religious education learning also has a very important role in instilling the values of multiculturalism to learners derived from the teachings of the Qur'an and hadith that are able to create learners who believe in and fear the almighty God. In addition, the purpose of implementation and values in the learning of Islamic religious education is so that learners can become people who have charitable competence in personal and social life.